Analysis of Community Ability and Access to Education as an Effort to Reduce Poverty Rate in Indonesia - Ida Harahap; Wati Rosmawati (Journal of Research in Business, Economics, and Education, 2021)
Poverty is a topic that is still being discussed in Indonesia. The mitigation itself cannot be carried out through one stage, so that poverty indicators need to be clearly, measurably and comprehensively defined and can then be guided and become the basis for making policies with precise targets with relevant poverty alleviation programs. In Indonesia, to accelerate poverty reduction, the Government has established social protection programs including the Prosperous Family Savings Program, the Smart Indonesia Program, and the Healthy Indonesia Program. The things that must be considered in doing so are public access to education and other factors, namely the average length of schooling and the unemployment rate.